Drawing drupes as a means of development of spatial thinking (Pedagogy of Higher and Secondary Education, 2009)
In the article typology and receptions of transmission of folds is crammed in the educational raising. The didactics value of picture of draperies as facilities of development of analytical thought of students is investigational. Essence of graphic analysis of plastic form opens up on the example of exposure оf forms of folds.
Keywords: types offolds; device offold; formations of fold; matter; fabri; drupes